2013
DOI: 10.18438/b8bs5p
|View full text |Cite
|
Sign up to set email alerts
|

Ethnographic Methods are Becoming More Popular in LIS Research

Abstract: the terms of the Creative Commons-Attribution-Noncommercial-Share Alike License 2.5 Canada (http://creativecommons.org/licenses/by-nc-sa/2.5/ca/), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly attributed, not used for commercial purposes, and, if transformed, the resulting work is redistributed under the same or similar license to this one. AbstractObjective -To determine the number of ethnographic studies of libraries and library users, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A criticism that has been levelled at the research by Khoo, et al (2012) was their interchangeable use of the terms 'ethnographic methods' and 'ethnographic studies' (Wakimoto, 2013), but it would appear that the former was used to mean methods that were employed ethnographically, that is, for an ethnographic study. As the authors consider participant observation to be a 'key' feature of such a study, one might therefore assume that the specific methods they identified in each study were employed (or reported to have been employed) by a participant observer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A criticism that has been levelled at the research by Khoo, et al (2012) was their interchangeable use of the terms 'ethnographic methods' and 'ethnographic studies' (Wakimoto, 2013), but it would appear that the former was used to mean methods that were employed ethnographically, that is, for an ethnographic study. As the authors consider participant observation to be a 'key' feature of such a study, one might therefore assume that the specific methods they identified in each study were employed (or reported to have been employed) by a participant observer.…”
Section: Literature Reviewmentioning
confidence: 99%